Acupuncture for adults with overactive bladder: a systematic review protocol - Mo, Qian (BMJ Open, 2015)
INTRODUCTION: Overactive bladder (OAB) is a symptom syndrome defined by the International Continence Society (ICS) as ‘the presence of urinary urgency (both daytime and nighttime), usually accompanied by increased frequency and nocturia with or without urge urinary incontinence in the absence of a urinary tract infection or other obvious pathology’. Clinical studies indicate that acupuncture could reduce micturition over 24 h, urgency episodes over 24 h, and improve quality of life among people with OAB. This systematic review protocol details the proposed methods for evaluating the effectiveness and safety of acupuncture for OAB. METHODS AND ANALYSIS: The following databases will be searched for relevant studies: the Cochrane Central Register of Controlled Trials (CENTRAL), the Cochrane Incontinence Group Trials Register, MEDLINE, EMBASE, Chinese Biomedical Literature Database (CBM), Chinese Medical Current Content (CMCC), Chinese Scientific Journal Database (VIP database), Wan-Fang Data, and China National Knowledge Infrastructure (CNKI) and will hand search a list of medical journals as a supplement. Any randomised controlled trials in English or Chinese without restriction of publication status will be included with treatment of OAB. Outcomes will mainly include number of micturition episodes over 24 h, number of urgency episodes over 24 h and number of incontinence episodes over 24 h. Two reviewers will independently screen the titles, abstracts or even full texts, and extract data. Two other reviewers will assess study quality. Revman 5.1 software will be used to conduct meta-analysis and calculate the risk ratio for dichotomous data. Weighted mean difference or standard mean difference will be calculated for continuous data. The Cochrane collaboration's tool will be used to assess the risk of bias. DISSEMINATION: This systematic review protocol will provide information on acupuncture therapy for OAB. The results will be disseminated through peer-reviewed publication or conference presentations. PROTOCOL REGISTRATION: PROSPERO CRD42014010181.